THE FEAR AND INSECURITY OF LIVING IN THE CITY - Hulse, Levi; Marcondes, Aldair; João Ferreira Monte, Mário (Ponto de Vista Jurídico, 2025)
This study aims to analyze aspects related to the fear and insecurity of living in urban environments, exploring their possible relationship with human behavior and globalized media content. Based on the three pillars of sustainability, the research is developed from the perspective of the social pillar, focusing specifically on the feeling of urban insecurity. According to the insights of Freud and Bauman, fear tends to be amplified by the dissemination of bad news, which leads some individuals to isolate themselves and invest in protective and security measures. Classical authors are referenced in an effort to portray humans as “political animals,” endowed with “souls full of passions,” who may be inclined toward crime and the violation of others’ rights in their pursuit of power and wealth. The study seeks to demonstrate that the feeling of insecurity is not necessarily related to a real increase in crime, but rather to the dissemination of biased media content that fuels, among other things, the private security market. Finally, the study argues that the State must become more present, punishing wrongdoers exemplarily and restoring a sense of safety, so that upright citizens can live without fear of their neighbors. Keywords: Sustainability. City. Insecurity. Fear.